Amorphous nanometer iron oxide combustion catalyst, preparation method and application

By preparing amorphous nano iron oxide combustion catalyst, the problem of limited activity of existing iron-based catalysts is solved, and the thermal decomposition and combustion performance of TKX-50 are significantly improved, achieving a more efficient combustion catalytic effect.

CN119431084APending Publication Date: 2025-02-14XIAN MODERN CHEM RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411720845.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The combustion catalytic activity of existing iron-based combustion catalysts is limited, and it is difficult to effectively regulate the combustion performance of GAP-based propellants containing TKX-50.

Method used

Amorphous nano iron oxide combustion catalyst was used to reduce the iron-containing inorganic salt solution and then calcined under an air atmosphere to obtain an amorphous nano iron oxide catalyst with a high specific surface area and a high porosity mesoporous structure.

Benefits of technology

It significantly improves the thermal decomposition and combustion performance of TKX-50, reduces the low-temperature decomposition peak and reduces the mild activation energy, shortens the laser ignition delay time, and improves the combustion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431084A_ABST
    Figure CN119431084A_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous nano iron oxide combustion catalyst, a preparation method and application, and the preparation method comprises the following steps: reducing an iron-containing inorganic salt solution with a reducing agent to prepare an iron oxide precursor, and calcining the iron oxide precursor in an air atmosphere to prepare the amorphous nano iron oxide combustion catalyst. The amorphous nano iron oxide combustion catalyst shows good catalytic activity for thermal decomposition of typical energetic components. The amorphous material is prepared by reducing the iron-containing inorganic salt solution through the reducing agent, so that the number of active sites on the surface is increased, and the catalytic activity of the amorphous nano iron oxide combustion catalyst is further improved; the amorphous nano iron oxide combustion catalyst provided by the invention has higher combustion catalysis performance for typical energetic components, so that the amorphous nano iron oxide combustion catalyst can be applied to the field of combustion catalysis of solid propellants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energetic materials, relates to a solid propellant combustion catalyst, and specifically relates to an amorphous nano iron oxide combustion catalyst, a preparation method and an application thereof. Background Art

[0002] Solid propellants, as an important part of the field of energetic materials, are the main power source for various solid engines such as strategic missiles, launch vehicles, and kinetic interception weapons. In the process of propellant production and application, once a safety accident occurs, it will bring significant losses. Therefore, the study of high-energy insensitive solid propellants is of great significance for improving the safety performance in the field of propellants. Compared with typical second-generation and third-generation energetic materials, TKX-50 has similar explosion heat and explosion pressure, but lower impact sensitivity and friction sensitivity. The use of TKX-50 in propellant applications can reduce sensitivity while maintaining high energy density, so TKX-50 has broad application prospects in GAP-based propellants. However, studies have shown that the burning rate pressure index of GAP-based propellants containing TKX-50 is relatively high, with the burning rate pressure index of the low-pressure section being 0.7-0.8 and the burning rate pressure index of the high-pressure section reaching up to 0.98. This further limits the application of TKX-50 in the field of propellants. At present, there are few reports on the research on the regulation of combustion performance of GAP-based propellants.

[0003] The use of combustion catalysts is an important means to regulate the combustion performance of solid propellants. It can not only increase the burning rate of solid propellants but also reduce the pressure index. Therefore, the development of new combustion catalysts has important theoretical significance and application value for improving the comprehensive performance of propellants. Thermal decomposition is generally considered to be the initial step of combustion, and the thermal decomposition performance has a significant effect on the combustion performance of solid propellants. Studying the catalytic effect of combustion catalysts on the thermal decomposition of TKX-50 is of great significance for regulating the combustion performance of GAP-based propellants containing TKX-50.

[0004] In the current research on the thermal decomposition of TKX-50 catalyzed by combustion catalysts, iron-based catalysts show excellent catalytic performance and can significantly reduce the decomposition temperature and activation energy. Zhang et al. studied the effect of Fe2O3 nanoparticles with different structures on the thermal decomposition performance of TKX-50. The results showed that tubular Fe2O3 exhibited the best catalytic activity, which reduced the low-temperature decomposition peak temperature by 36.5°C and significantly reduced the activation energy. The team also synthesized rGO-Fe2O3 nanocomposites with different structures and applied them to the thermal decomposition of TKX-50. The results showed that compared with pure TKX-50, the peak temperature and apparent activation energy of thermal decomposition with the addition of rGO-Fe2O3 were reduced by 40.0°C and 28.1 kJ mol, respectively. -1Zhang et al. prepared h-Fe2O3@rGO, s-Fe2O3@rGO, and rGO and Fe2O3 nanoparticles and investigated their catalytic effects on TKX-50. The results showed that s-Fe2O3@rGO exhibited the best catalytic activity, reducing the low-temperature decomposition peak by 40.7°C and increasing the decomposition heat by 1008 J·g -1 However, the limited number of active sites on the catalyst surface still restricts the further application of iron-based catalysts. Therefore, it is necessary to find effective ways to further improve the catalytic activity of iron-based catalysts.

[0005] Among many nanomaterials, amorphous nanomaterials have attracted more and more attention in recent years. Compared with crystalline materials, amorphous nanomaterials have a series of high-density unsaturated coordination sites on their surfaces due to their irregularly arranged atomic structure, which is conducive to the adsorption and activation of molecules such as reactants and intermediates, thus showing better catalytic performance. At present, amorphous nanomaterials show certain application prospects in the field of photoelectrocatalysis, but there are relatively few studies in the field of solid propellants, and there is currently a lack of mass production synthesis strategies for amorphous nano iron oxide catalysts. The introduction of amorphous nano iron oxide catalysts provides a new direction for the synthesis of solid propellant combustion catalysts, and is expected to achieve efficient catalysis in the field of solid propellants. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an amorphous nano iron oxide combustion catalyst, a preparation method and an application thereof, so as to solve the technical problem that the combustion catalytic activity of the iron-based combustion catalyst in the prior art is limited. The method can effectively increase the specific surface area and the number of active sites of the iron oxide, so that the thermal decomposition performance and combustion performance of TKX-50 are further improved.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0008] A method for preparing an amorphous nano iron oxide combustion catalyst comprises the following steps: firstly reducing an inorganic salt solution containing iron to obtain an iron oxide precursor, and then calcining the iron oxide precursor in an air atmosphere to obtain an amorphous nano iron oxide combustion catalyst; the calcination conditions are: heating to 100-300°C at a heating rate of 5-20°C / min, and then calcining at a temperature of 100-300°C for 1-3h.

[0009] The present invention also includes the following technical features:

[0010] Specifically, the following steps are included:

[0011] Step A, dispersing an inorganic salt containing iron and a surfactant in a solvent to obtain a mixed solution 1;

[0012] Step B, dispersing a reducing agent and an alkaline raw material in a solvent to obtain a mixed solution 2;

[0013] Step C, after the mixed solution 1 is fully stirred and dissolved, the mixed solution 2 is quickly added to the mixed solution 1 to obtain a reaction solution;

[0014] Step D, after the reaction is completed, the reaction solution is centrifuged, washed, and freeze-dried to obtain a reaction product;

[0015] Step E: heat-treating the reaction product under high temperature conditions to obtain an amorphous nano-iron oxide catalyst.

[0016] Specifically, in step A:

[0017] The iron-containing inorganic salt is selected from any one of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ammonium ferrous sulfate, ferric chloride, and ferrous chloride;

[0018] The surfactant is selected from any one of polytetraethylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, cetrimonium chloride, octadecyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, methyltrioctylammonium chloride, benzalkonium bromide, tetramethylammonium iodide, tetrabutylammonium fluoride, tetrabutylammonium chloride, lauryltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, and di-C8-10 quaternary ammonium salt;

[0019] The solvent is deionized water.

[0020] Specifically, in step B:

[0021] The reducing agent is selected from any one of sodium cyanoborohydride, sodium triacetoxyborohydride, sodium tris(trifluoroacetyl)borohydride, sodium borohydride, lithium borohydride, zinc borohydride, lithium triethylborohydride, N,N-dimethylamino lithium borohydride, diisobutyl sodium hydride, diisobutylaluminum hydride, lithium aluminum hydride, dimethyl sulfide borane, THF borane, triethylsilane, and dimethoxyethoxyaluminum hydride;

[0022] The alkaline raw material is selected from any one of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, strontium hydroxide, calcium hydroxide, barium hydroxide, thallium hydroxide, diammine silver hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water;

[0023] The solvent is deionized water.

[0024] Specifically, in step A, the mass fraction of the surfactant in the iron-containing inorganic salt is 30% to 40%; in step B, the molar ratio of the reducing agent to the alkaline raw material is 1:1 to 2:1.

[0025] Specifically, the step D comprises: washing the reaction solution with anhydrous ethanol and deionized water for 3 to 6 times by centrifugation, and freeze-drying for 48 to 72 hours.

[0026] Specifically, the step E comprises: heat treating the reaction product in an air atmosphere at a temperature of 200 to 300° C. for a time of 60 to 180 minutes.

[0027] An amorphous nano-iron oxide combustion catalyst is prepared by the preparation method of the amorphous nano-iron oxide combustion catalyst; the amorphous nano-iron oxide combustion catalyst has a high specific surface area and a high porosity mesoporous structure, and the specific surface area is 198m 2 / g; the average mesopore size is 0.87cm 3 / g.

[0028] The amorphous nano iron oxide combustion catalyst is used for adding into TKX-50 to prepare a mixture containing the amorphous nano iron oxide combustion catalyst, and the addition amount of the amorphous nano iron oxide combustion catalyst is 0.5% to 2% of the mass of TKX-50.

[0029] Specifically, the mixture is heated to 10 K·min -1 The low temperature decomposition peak temperature of the heating rate is 212.2℃; at 51W / cm 2 The laser ignition delay time under the laser power density is less than or equal to 100ms; at 306W / cm 2 The laser ignition delay time under the laser power density is less than or equal to 25ms.

[0030] Compared with the prior art, the present invention has the following technical effects:

[0031] (I) Compared with the prior art, the present invention provides an application of an amorphous nano-iron oxide catalyst in the field of thermal decomposition and combustion of energetic materials. Compared with crystalline catalysts, the defects exposed by the irregularly arranged atomic structure on the surface of amorphous materials can serve as active sites, and exhibit excellent catalytic activity for the decomposition of energetic materials through adsorption and activation of intermediate molecules.

[0032] (II) The raw materials used in the preparation method of the amorphous nano-iron oxide combustion catalyst of the present invention are all low-priced and easily available. The preparation process is simple, controllable, mild in preparation conditions, low in energy consumption, and economical and environmentally friendly.

[0033] (III) The amorphous nano-iron oxide combustion catalyst prepared by the present invention has a microscopic morphology of a stacked nano-sheet structure with a high specific surface area. The nano-iron oxide contains abundant surface active sites and has excellent combustion catalytic activity.

[0034] (Ⅳ) Experiments show that amorphous nano-iron oxide exhibits excellent catalytic performance for the thermal decomposition of TKX-50. -1 Under the conditions of a catalyst mass ratio of 98:2, the low-temperature decomposition peak temperature of the amorphous nano-iron oxide catalyst is 212.2°C, which is lower than the low-temperature peak temperature of the commercial nano-iron oxide catalyst (218.9°C), reflecting its excellent catalytic activity for the thermal decomposition of TKX-50. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the SEM picture of the amorphous nano-iron oxide combustion catalyst in the embodiment.

[0036] Figure 2 HRTEM image of the amorphous nano-iron oxide combustion catalyst in the embodiment.

[0037] Figure 3 It is the adsorption-desorption curve diagram of the amorphous nano-iron oxide combustion catalyst in the embodiment.

[0038] Figure 4 Graph showing the pore size distribution of the amorphous nano-iron oxide combustion catalyst in the embodiment.

[0039] Figure 5 It is the XRD diagram of the amorphous nano-iron oxide combustion catalyst in the embodiment.

[0040] Figure 6 This is the EDS image of the amorphous nano-iron oxide combustion catalyst, where the atomic percentages of iron and oxygen are shown in the figure.

[0041] Figure 7 This is the DSC curve of amorphous nano-iron oxide, commercial nano-iron oxide material and TKX-50 mixed in a ratio of 98:2 at 10℃ / min.

[0042] Figure 8 This is the ignition delay time curve of amorphous nano-iron oxide, commercial nano-iron oxide material and TKX-50 mixed in a ratio of 98:2.

[0043] Fig. 9 The amorphous nano-iron oxide, commercial nano-iron oxide and TKX-50 were mixed in a ratio of 98:2 and then the laser power was 51 W·cm -2 The flame development process. DETAILED DESCRIPTION

[0044] The present invention provides an amorphous nano iron oxide combustion catalyst, a preparation method and an application thereof, which is obtained by reducing a reducing agent and an inorganic salt containing iron under alkaline conditions, and has a structure of two-dimensional lamellar amorphous nano iron oxide. The amorphous nano iron oxide catalyst can effectively give play to the characteristics of the high number of active sites on the surface of amorphous materials, improve the thermal decomposition and ignition performance of energetic materials through the rich unsaturated coordination environment on the surface, and solve the technical problem of limited catalytic performance of existing iron-based nano combustion catalysts for solid propellants. The amorphous nano iron oxide material prepared by the present invention has high combustion catalytic performance for energetic materials and can be used for combustion catalysis of solid propellants.

[0045] In the present invention, TKX-50 is the abbreviation of 1,1'-dihydroxy-5,5'-bi-tetrazolyl dihydroxy ammonium salt.

[0046] The method for preparing the amorphous nano-iron oxide combustion catalyst comprises the following steps:

[0047] Step A, dispersing an inorganic salt containing iron and a surfactant in a solvent to obtain a mixed solution 1;

[0048] Step B, dispersing a reducing agent and an alkaline raw material in a solvent to obtain a mixed solution 2;

[0049] Step C, after the mixed solution 1 is fully stirred and dissolved, the mixed solution 2 is quickly added to the mixed solution 1 to obtain a reaction solution;

[0050] Step D, after the reaction is completed, the reaction solution is centrifuged, washed, and freeze-dried to obtain a reaction product;

[0051] Step E: heat-treating the reaction product under high temperature conditions to obtain an amorphous nano-iron oxide catalyst.

[0052] Wherein, the inorganic salt containing iron is selected from any one of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ammonium ferrous sulfate, ferric chloride, and ferrous chloride;

[0053] The surfactant is selected from any one of polytetraethylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, cetrimonium chloride, octadecyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, methyltrioctylammonium chloride, benzalkonium bromide, tetramethylammonium iodide, tetrabutylammonium fluoride, tetrabutylammonium chloride, lauryltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, di-C8-10 quaternary ammonium salt, and octadecyltrimethylammonium bromide;

[0054] The reducing agent is selected from any one of sodium cyanoborohydride, sodium triacetoxyborohydride, sodium tri(trifluoroacetyl)borohydride, sodium borohydride, lithium borohydride, zinc borohydride, lithium triethylborohydride, N,N-dimethylamino lithium borohydride, diisobutyl sodium hydride, diisobutylaluminum hydride, lithium aluminum hydride, dimethyl sulfide borane, THF borane, triethylsilane, and dimethoxyethoxyaluminum hydride;

[0055] The alkaline raw material is selected from any one of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, strontium hydroxide, calcium hydroxide, barium hydroxide, thallium hydroxide, diammine silver hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water.

[0056] The mass fraction of the surfactant in the iron-containing inorganic salt is 30% to 40%, preferably 37% in the present invention, and the molar ratio of the reducing agent to the alkaline raw material is 1:1 to 2:1, preferably 2:1 in the present invention.

[0057] The solvent is selected from deionized water.

[0058] In the mixed solution, the mass volume ratio of the inorganic salt to the solvent is 300-500 mg:10-15 mL, preferably 300 mg:10 mL, 400 mg:10 mL, 500 mg:10 mL, or any value between 300-500 mg:10-15 mL.

[0059] The mass volume ratio of the reducing agent to the solvent is 150-200 mg:10-15 mL, preferably 150 mg:10 mL, 175 mg:10 mL, 200 mg:10 mL, or any value between 150-200 mg:10-15 mL.

[0060] The present invention has no particular limitation on the mixing method, but magnetic stirring mixing is preferred.

[0061] After being uniformly mixed, the mixed solution 2 is quickly added to the mixed solution 1, and the mixture is fully reacted at a certain temperature to obtain a reaction solution.

[0062] In the present invention, the mass ratio of the iron-containing inorganic salt to the reducing agent is 5:1 to 7:1, preferably 5:1, 6:1, 7:1, or any value between 5:1 and 7:1. The reaction temperature is 40 to 60°C, preferably 40, 50, 60°C, or any value between 40 and 60°C. The reaction time is 30 to 60 min, preferably 30, 40, 50, 60 min, or any value between 30 and 60 min.

[0063] After sufficient reaction, the reaction solution is centrifuged, washed, and then freeze-dried to obtain a dry product.

[0064] In the present invention, washing is to centrifuge the reaction product with ethanol and deionized water for 3 to 6 times in sequence; the speed of the centrifuge is 4000 to 6000 r·min -1 , preferably 4000, 5000, 6000 r·min -1 , or 4000~6000r·min -1 The centrifugation time is 3 to 5 min, preferably 3, 4, 5 min, or any value between 3 and 5 min. Drying is carried out under air atmosphere conditions, the drying temperature is -30 to -50°C, preferably -30, -35, -40, -45, -50°C, or any value between -30 and -50°C, and the freeze-drying time is 48 to 72 hours. In the present invention, drying is preferably carried out in a freeze dryer.

[0065] The dried product is heat-treated to obtain a heat-treated product.

[0066] Wherein, the heat treatment is carried out in air atmosphere, the temperature of the heat treatment is 200-300°C, preferably 200, 250, 300°C, or any value between 200-300°C, and the time of the heat treatment is 60-180min, preferably 60, 90, 150, 180min, or any value between 60-180min. In the present invention, the heat treatment is preferably carried out in a tubular furnace. Finally, after the heat treatment is completed, an amorphous nano iron oxide combustion catalyst is obtained.

[0067] The amorphous nano iron oxide catalyst provided by the present invention has a simple synthesis method, excellent performance and low price. In addition, the amorphization strategy is a general method, not limited to iron-containing inorganic salts, and various metal inorganic salts can be used as metal sources. By using inorganic salts as templates and controlling the calcination temperature of the synthesis process between the decomposition temperature and the crystallization temperature, various metal amorphous nanosheets can be successfully prepared.

[0068] The amorphous nano-iron oxide combustion catalyst prepared by the above-mentioned preparation method has a high specific surface area and a high porosity mesoporous structure, with a specific surface area of ​​198m 2 / g; the average mesopore size is 0.87cm 3 / g.

[0069] The above-mentioned amorphous nano-iron oxide combustion catalyst is used for adding into TKX-50 to prepare the mixture containing amorphous nano-iron oxide combustion catalyst, and the addition amount of amorphous nano-iron oxide combustion catalyst is 0.5% to 2% of the mass of TKX-50.

[0070] The mixture was heated to 10 K·min -1The low-temperature decomposition peak temperature of the heating rate is 212.2℃, which is 27.0℃ lower than that of pure TKX-50. a Reduced by 10.4 kJ·mol -1 ; at 51W / cm 2 The laser ignition delay time under laser power density is less than or equal to 100ms, which is 320ms shorter than that of pure TKX-50. 2 The laser ignition delay time under laser power density is less than or equal to 25ms, which is 28ms shorter than that of pure TKX-50.

[0071] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0072] Example:

[0073] This embodiment provides an amorphous nano-iron oxide combustion catalyst and a preparation method thereof, which specifically comprises the following steps:

[0074] 40mMol ferric nitrate nine hydrate and 26mMol hexadecyl trimethyl ammonium bromide were uniformly mixed in 500ml deionized water under stirring to form a mixed solution 1. Then 80mMol sodium borohydride and 40mMol sodium hydroxide were uniformly mixed in 200ml deionized water under stirring to form a mixed solution 2. Mixed solution 2 was quickly added to mixed solution 1 and allowed to react at 40°C for 30min. The reaction solution was then centrifuged and washed with deionized water and anhydrous ethanol for 3 times, respectively, and the washed reactants were freeze-dried for 48h. The dried reactants were placed in a tubular furnace and calcined at 240°C for 90min to finally obtain a brown-red amorphous nano-iron oxide combustion catalyst.

[0075] The amorphous nano-iron oxide combustion catalyst prepared in this example is characterized as follows:

[0076] Figure 1 This is a SEM spectrum of the amorphous nano-iron oxide combustion catalyst in this example. As shown in the figure, the result clearly shows that the amorphous nano-iron oxide presents a stacked lamellar morphology.

[0077] Figure 2 This is a HRTEM image of the amorphous nano-iron oxide combustion catalyst in this example, which shows that the prepared nano-iron oxide is a nano-sheet with a high specific surface area and a diameter of about 400-700 nm.

[0078] Figure 3 is the adsorption-desorption curve of the amorphous nano-iron oxide combustion catalyst in this embodiment, Figure 3In the figure, “γ-Fe2O3” refers to commercial nano-iron oxide catalyst, and “Ra-Fe2O3” refers to amorphous nano-iron oxide combustion catalyst. The specific surface area of ​​the amorphous nano-iron oxide combustion catalyst reaches 198m 2 / g, much higher than commercial nano iron oxide catalysts (50m 2 / g), indicating that the synthesized amorphous nano-iron oxide combustion catalyst has a high specific surface area.

[0079] Figure 4 is the pore size distribution diagram of the amorphous nano-iron oxide combustion catalyst in this embodiment, Figure 4 In the figure, “γ-Fe2O3” refers to commercial nano-iron oxide catalyst, and “Ra-Fe2O3” refers to amorphous nano-iron oxide combustion catalyst. The average pore volume of the amorphous nano-iron oxide combustion catalyst reaches 0.87 cm 3 / g, much higher than commercial nano iron oxide catalysts (0.29cm 3 / g), indicating that the synthesized amorphous nano-iron oxide combustion catalyst has a macroporous structure.

[0080] Figure 5 It is the XRD diagram of the amorphous nano-iron oxide combustion catalyst in the embodiment. Figure 5 In the figure, “γ-Fe2O3” refers to commercial nano-iron oxide catalyst, and “Ra-Fe2O3” refers to amorphous nano-iron oxide combustion catalyst. Figure 5 It can be seen that the amorphous nano-iron oxide combustion catalyst does not show obvious diffraction peaks. However, commercial nano-iron oxide shows good crystallinity, which is consistent with the standard PDF card (JCPDS NO.39-1346), indicating that the synthesized amorphous nano-iron oxide combustion catalyst has good amorphous properties.

[0081] Figure 6 This is the EDS image of amorphous nano-iron oxide combustion catalyst. Figure 6 In the equation, “Fe” represents the element iron and “O” represents the element oxygen. Figure 6 It shows that the main elements of the amorphous nano-iron oxide combustion catalyst include iron and oxygen, and the atomic content ratio is about 2:3, indicating that the synthesized amorphous nano-iron oxide combustion catalyst is an iron oxide structure.

[0082] The performance test of the amorphous nano-iron oxide combustion catalyst of this embodiment is as follows:

[0083] Figure 7 The DSC curves of amorphous nano-iron oxide, commercial nano-iron oxide and TKX50 mixed in a ratio of 98:2 at 10℃ / min; Figure 7In the figure, "Ra-Fe2O3+TKX-50" represents a mixture of amorphous nano-iron oxide and TKX-50, "γ-Fe2O3+TKX-50" represents a mixture of commercial nano-iron oxide and TKX-50, and "TKX-50" represents pure TKX-50 material without any catalyst. The addition of amorphous nano-iron oxide reduces the low-temperature decomposition peak temperature of TKX50 by 24.9°C, and the high-temperature decomposition peak gradually overlaps with the low-temperature decomposition peak. Compared with commercial nano-iron oxide, the synthesized amorphous nano-iron oxide exhibits better catalytic effect.

[0084] The TKX-50 containing amorphous nano-iron oxide was used as the experimental group, the TKX-50 containing commercial nano-iron oxide was used as the control group, and the pure TKX-50 without catalyst was used as the blank control group. Laser ignition tests were performed under different laser power densities. The ignition delay time test results are shown in Figure 2. Figure 8 As shown, the flame propagation image is Fig. 9 shown. Figure 8 Among them, “Ra-Fe2O3+TKX-50” represents a mixture of amorphous nano-iron oxide and TKX-50, “γ-Fe2O3+TKX-50” represents a mixture of commercial nano-iron oxide and TKX-50, and “TKX-50” represents pure TKX-50 material without any catalyst. Fig. 9 In the table, "Ra-Fe2O3+TKX-50" represents a mixture of amorphous nano-iron oxide and TKX-50, "γ-Fe2O3+TKX-50" represents a mixture of commercial nano-iron oxide and TKX-50, and "TKX-50" represents pure TKX-50 material without any catalyst. Figure 8 It can be seen that under the same test conditions, the ignition delay time of the experimental group, the control group and the blank control group all showed a decreasing trend with the increase of power density. Compared with the blank control group, the ignition delay time of the experimental group at low laser power density was significantly shortened, and the laser ignition energy was significantly reduced, 51W / cm 2 The laser ignition delay time under power density decreased from 410ms to 100ms, which was lower than the ignition delay time of the control group (122ms), indicating that amorphous nano-iron oxide showed better catalytic performance than commercial nano-iron oxide. Fig. 9 It can be seen that under the same power density, compared with the control group and the blank control group, the flame propagation speed of the experimental group increased, the flame brightness became significantly larger, and the duration increased. This shows that the synthesized amorphous nano-iron oxide exhibits the most excellent catalytic effect and can greatly improve the combustion performance of TKX-50.

Claims

1. A method for preparing an amorphous nano-iron oxide combustion catalyst, characterized in that: The iron-containing inorganic salt solution is first reduced to obtain an iron oxide precursor, and then the iron oxide precursor is calcined in an air atmosphere to obtain an amorphous nano-iron oxide combustion catalyst; the calcination conditions are: heating to 100-300°C at a heating rate of 5-20°C / min, and calcining at a temperature of 100-300°C for 1-3h.

2. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 1, characterized in that: The following steps are involved: Step A, dispersing an inorganic salt containing iron and a surfactant in a solvent to obtain a mixed solution 1; Step B, dispersing a reducing agent and an alkaline raw material in a solvent to obtain a mixed solution 2; Step C, after the mixed solution 1 is fully stirred and dissolved, the mixed solution 2 is quickly added to the mixed solution 1 to obtain a reaction solution; Step D, after the reaction is completed, the reaction solution is centrifuged, washed, and freeze-dried to obtain a reaction product; Step E: heat-treating the reaction product under high temperature conditions to obtain an amorphous nano-iron oxide catalyst.

3. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 2, characterized in that: In step A: The iron-containing inorganic salt is selected from any one of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ammonium ferrous sulfate, ferric chloride, and ferrous chloride; The surfactant is selected from any one of polytetraethylammonium bromide, benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, cetrimonium chloride, octadecyltrimethylammonium chloride, octadecyldimethylbenzylammonium chloride, methyltrioctylammonium chloride, benzalkonium bromide, tetramethylammonium iodide, tetrabutylammonium fluoride, tetrabutylammonium chloride, lauryltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dioctadecyldimethylammonium chloride, and di-C8-10 quaternary ammonium salt; The solvent is deionized water.

4. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 2, characterized in that: In the step B: The reducing agent is selected from any one of sodium cyanoborohydride, sodium triacetoxyborohydride, sodium tris(trifluoroacetyl)borohydride, sodium borohydride, lithium borohydride, zinc borohydride, lithium triethylborohydride, N,N-dimethylamino lithium borohydride, diisobutyl sodium hydride, diisobutylaluminum hydride, lithium aluminum hydride, dimethyl sulfide borane, THF borane, triethylsilane, and dimethoxyethoxyaluminum hydride; The alkaline raw material is selected from any one of lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, strontium hydroxide, calcium hydroxide, barium hydroxide, thallium hydroxide, diammine silver hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water; The solvent is deionized water.

5. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 2, characterized in that: In the step A, the mass fraction of the surfactant in the iron-containing inorganic salt is 30% to 40%; in the step B, the molar ratio of the reducing agent to the alkaline raw material is 1:1 to 2:

1.

6. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 2, characterized in that: The step D comprises: washing the reaction solution with anhydrous ethanol and deionized water for 3 to 6 times by centrifugation, and freeze-drying for 48 to 72 hours.

7. The method for preparing the amorphous nano-iron oxide combustion catalyst according to claim 2, characterized in that: The step E comprises: heat treating the reaction product in an air atmosphere at a temperature of 200 to 300° C. for a time of 60 to 180 minutes.

8. An amorphous nano-iron oxide combustion catalyst, characterized in that: The amorphous nano-iron oxide combustion catalyst is prepared by the preparation method of any one of claims 1 to 7; the amorphous nano-iron oxide combustion catalyst has a high specific surface area and a high porosity mesoporous structure, with a specific surface area of ​​198m 2 / g; the average mesopore size is 0.87cm 3 / g.

9. Use of the amorphous nano-iron oxide combustion catalyst according to claim 8 for adding to TKX-50 to prepare a mixture containing the amorphous nano-iron oxide combustion catalyst, wherein the amount of the amorphous nano-iron oxide combustion catalyst added is 0.5% to 2% of the mass of TKX-50.

10. The use according to claim 9, characterized in that The mixture was heated to 10 K·min -1 The low temperature decomposition peak temperature of the heating rate is 212.2℃; at 51W / cm 2 The laser ignition delay time under the laser power density is less than or equal to 100ms; at 306W / cm 2 The laser ignition delay time under the laser power density is less than or equal to 25ms.